Delfinoterapia w usprawnianiu dzieci z zaburzeniami w rozwoju – dylematy i kontrowersje - Buchnat, Marzena; Rzepka, Michał (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
Dolphin-Assisted Therapy (DAT) is a form of combined therapy – aquatic therapy and animal-assisted therapy, where the patient is in close contact with the dolphin. In such therapy the dolphin is a partner, a motivator and a kind of reward for the child. It must be noted, however, that the basis of its effectiveness is the intensive child’s cooperation with the therapist. During the course of professional dolphin therapy, in addition to in-water session, there are also classroom activities, where motivation and skills gained during training with the animal are used, consolidated and expanded. With such planned therapy, effects may relate to the physical as well as emotional and cognitive sphere, depending on the planned activity, which the therapist is focused on.